Damage detection using parameter dependent dynamic experiments and wavelet transformation - Garstecki, Andrzej; Knitter‐Piatkowska, Anna; Pozorski, Zbigniew; Ziopaja, Krzysztof (Journal of Civil Engineering and Management, 2004)
The paper deals with a class of problems, where localised damage is detected using static and dynamic tests. Response of a structure is analysed employing discrete wavelet transformation as a tool for signal processing. The localised damage in beam structures was modelled as bending stiffness reduction. The efficiency of static and dynamic tests is studied. The minimal number of experimental measurement data and the precision of measurements required for the successful damage localisation is discussed by several numerical examples. First Published Online: 14 Oct 2010